Evaluation of Community Health Volunteers Training on Early Detection Skills of Pulmonary Tuberculosis - Muhamad Jauhar; Siti Wahyuni; Sri Widiyati; Arwani Arwani (Poltekkes Kemenkes Semarang, 2022)
Background: achievement of coverage numbers of cases of pulmonary TB cases that meet the target impact on the prevention of disease transmission, complications, and even death due to pulmonary TB. Increasing the capacity of community health volunteers as partners of health workers in the early detection of pulmonary TB becomes a program that needs to be considered.Purpose: this study aims to identify the effect of community health volunteer training on the early detection of pulmonary tuberculosis.Methods: the study design used quasi-experimental pre-test and post-test types with a control group. The study was conducted in February-March 2020 in the working area of the Kutowinangun Primary Health Care Facilities. The total sample of 32 community health volunteers for each intervention and control group was selected by purposive sampling based on inclusion and exclusion criteria. The instruments used were observation sheets and modules developed by researchers. The training was conducted in 5 sessions over 5 days with a duration of 60 minutes per session. Data analysis using paired t-test and independent t-test. This research has passed the ethical test from the Ethics Committee of the Faculty of Public Health, University of Muhammadiyah Semarang.Results: there was an effect of community health volunteers' training on improving early TB pulmonary detection skills significantly with a p-value = 0,000 (p 0.05).Conclusion: refreshments of community health volunteers must be planned in the annual work plan program design. Increased skills have a positive impact on the increasing findings of new cases of pulmonary TB. Community health volunteer training can be integrated with the DOTS program in primary health care facilities.